Factors Influencing iPad Acceptance in Mandatory Conditions by Students: Cross-Classes Analysis - Sarosa, Samiaji; Retno Setyowati, Agustina (INTENSIF: Jurnal Ilmiah Penelitian dan Penerapan Teknologi Sistem Informasi, 2020)
This article is investigating the acceptance of the iPad among new students at a university. IPad usage is compulsory, and the purchase is part of the new student admission package. Two previous surveys using UTAUT have shown mixed results. The author decided to use survey results from both studies and reanalyze the questionnaire's answers. Data analysis was conducted using the SEM-PLS tool. The result showed only Anxiety and Self-Efficacy influencing Intention to Use while Intention to Use and Facilitating Condition influencing the use of iPad. The relation between Self-Efficacy and Intention to Use was moderated by gender, while the relationship between Intention to Use and Usage was moderated by experience in using a tablet.